Indigenous Water Symbolism and Management: A Comparative Study on Ecologies of Rain and Intellectual Appropriation in Bangladesh, India, the US, and Germany - Rahman, Md Habibur; Md. Mobashir Rahman; Imroze Asif Khan (HISTORICAL: Journal of History and Social Sciences, 2025)
Indigenous and folk water representations are examined using the conceptual lenses "Rainline" and "Waterline," which investigate how rain interacts symbolically and pragmatically in environmental traditions. The study contrasts eco-critical research from Bangladesh, India, the US, and Germany to examine how songs, rituals, myths, and proverbs reflect cultural reactions to rain and water as sacred and ecological requirements. The studies center on Bangladesh's Garo, Santal, and Rajbongshi people, Indian tribal and Vedic rain customs, Native American rain invasions, and European farming. Various societies both cognitively modify and symbolically control natural forces. In emotional and agricultural life, rainfall is required, negotiated, and acknowledged; these ideas help to organize these symbolic surroundings. The article combines folklore research, thematic coding, and comparative cultural hermeneutics. These approaches are not relics; they assert that they are dynamic ecological knowledge systems with sustainable knowledge. It suggests considering localized, culturally informed responses to water and temperature as means of climate adaptation.